2018
DOI: 10.1007/s11886-018-1049-9
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hours and Risk of Cardiovascular Disease

Abstract: Purpose of ReviewTo summarize the evidence on the relationship between long working hours and cardiovascular disease, such as coronary heart disease and stroke.Recent FindingsLarge-scale meta-analyses with published and individual participant observational data on more than 740,000 men and women free of cardiovascular disease report a link between long working hours (≥ 55 h a week) and the onset of cardiovascular events. Our meta-analytic update of summary evidence suggests a 1.12-fold (95% CI 1.03–1.21) incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
78
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 46 publications
5
78
0
4
Order By: Relevance
“…Long working hours, defined as exceeding h/day at work or greater than 40 h of work a week, are considered to cause workers' physical and psychological health problems, including cardiovascular disease 1,2) , high blood pressure 3,4) , sleep disruption 5) , diabates 6,7) , metabolic syndrome 8,9) , fatigue 10) , injury 11) , depression 12,13) , and other health disorders 14,15) . In Japan, the issue of long working hours has been seriously discussed since the late 1980s because some workers died after they overworked for some duration.…”
Section: Introductionmentioning
confidence: 99%
“…Long working hours, defined as exceeding h/day at work or greater than 40 h of work a week, are considered to cause workers' physical and psychological health problems, including cardiovascular disease 1,2) , high blood pressure 3,4) , sleep disruption 5) , diabates 6,7) , metabolic syndrome 8,9) , fatigue 10) , injury 11) , depression 12,13) , and other health disorders 14,15) . In Japan, the issue of long working hours has been seriously discussed since the late 1980s because some workers died after they overworked for some duration.…”
Section: Introductionmentioning
confidence: 99%
“…This increasing trend represents a public health problem because of the number and variety of related adverse health consequences. Abundant scientific evidence indicates that long work hours may lead to or are associated with physical and psychological health problems including cardiovascular disease (CVD) . Long work hours may also lead to poor lifestyle behaviors such as insufficient leisure‐time physical activity, less healthy dietary intake, and inadequate sleep duration that not only affects quality of life, but are also associated with adverse health conditions .…”
Section: Introductionmentioning
confidence: 99%
“…From the Whitehall II study, Kivimaki et al demonstrated that data on working hours may improve risk prediction of coronary heart disease (CHD) using the Framingham risk score in low‐risk, working populations. According to a recent meta‐analysis, the evidence that long working hours are a risk factor for CVD suggests a small increased risk associated with CHD (relative risk: 1.12 [95% confidence interval: 1.03‐1.21] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former mechanism includes psychosocial stress, physical (noise), and the chemical (dust and toxic chemicals) environment. The latter includes lack of sleep and physical activity . These upstream factors are thought to induce behavioral mechanisms (eg, over eating and drinking alcohol), followed by then clinical stage before manifesting CVD (eg, high blood pressure, dyslipidemia, diabetes, inflammation, atrial fibrillation, and hypercoagulability).…”
mentioning
confidence: 99%